Effect of Cobactin on the feedlot performance and carcass traits of beef steers - Corah, L.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The addition of Cobactin to feedlot rations had no significant effect on average daily gain or feed efficiency, but did improve quality grade of steers fed for 110 days.
Keywords: Beef; Cobactin; Feedlot performance; Carcass traits; Steers